HUBUNGAN KEPEMIMPINAN, MOTIVASI DAN KOMPENSASI DENGAN KEPUASAN KERJA PERAWAT RAWAT INAP RSUD PURI HUSADA TEMBILAHAN TAHUN 2017 - Esqha „Arini (JURNAL ILMIAH MAKSITEK, 2018)
Satisfaction is an emotional condition which is favorable or unfavorable for employees concerning their jobs. It is related to leadership style, work motivation, and compensation. The objective of the research was to find out the correlation of leadership, motivation, and compensation with work satisfaction of nurses in the Inpatient Wards of RSUD Puri Husada, Tembilahan, in 2017.The research used analytic method with cross sectional design. The population was 108 inpatient and outpatient nurses at RSUD Puri Husada, Tembilahan, and 85 of them were used as the samples, using total population sampling technique.The result of bivariate analysis with chi square statistic test at α=0.05 showed that there was the correlation of leadership (p=0.000), motivation (p=0.00), and compensation (p=0.001) with work satisfaction. The result of multivariate analysis with logistic regression test showed that the variable which had the most dominant influence on inpatient nurses’ work satisfaction was leadership (p=0.023; OR=3.356).